Relationship Between Satisfaction With Medical Care, Physical Health, and Emotional Well-Being in Adult Men: Mediating Role of Communication - Cristian Ramos-Vera; Jacksaint Saintila; Yaquelin E. Calizaya-Milla; María Elena Acosta Enríquez; Antonio Serpa Barrientos (SAGE Publishing, 2022)
Background: Non-communicable diseases and psychiatric pathologies are the health problems that most affect the population in the United States. Objective: This study aimed to examine the mediating role of patient-centered communication (PCC) in the relationship between satisfaction with medical care, physical health, and emotional well-being in American men. Methods: A cross-sectional - predictive study was carried out. The variables analyzed were satisfaction with medical care, physical health, and emotional well-being. Information from the Health Information National Trends Survey Data (HINTS) was used; HINTS 5, cycle 3 (collected between January and June 2019) and 4 (2020). Data from 3338 men were considered (mean age: M  = 55.40, SD = 19.53). Data analyses were carried out using structural equation modeling (SEM) to represent the statistical mediation model with latent and observable variables. Results: Analyses showed that the variables were significantly related ( P  < .01). In the mediation model, there is evidence that satisfaction predicts communication (β = .764, P  < .001) and this, in turn, is related to physical health (β = .079, P  = .007) and emotional well-being (β = .145, P  < .001). In addition, the standardized estimates of the structural multiple mediation model presented acceptable goodness-of-fit indices: χ 2 /gl = 2.24, CFI = 0.999, TLI = 0.999, RMSEA = 0.019 [90% CI: 0.013-0.022], SRMR = 0.018. Conclusion: Patient-centered communication plays a significant dual mediating role in the relationship between satisfaction with medical care, physical health, and emotional well-being, respectively. Therefore, PCC is essential in healthcare for American men.